Literary Cartography of Performance Ecologies in Sheela Tomy’s "Valli" - Nataraj, Shilpa; Narayana, Sharmila (SARE: Southeast Asian Review of English, 2024)
The present era, marked by the onset of posthumanism, is not just an antithesis to humanism but a return to a pre-humanism era where the aspects of the non-human and human existed. As a result, themes of blurring boundaries between humans and other species, climate catastrophes and ecological crises are predominantly narrativised, propelling us to look at the entanglements of human narratives, realities of geography, environment and history in studying sites of literature through the framework of performance ecologies provided by Jeff Grygny. Sheela Tomy’s Valli is one of the most recent in creating ecological awareness. In the picturesque setting of the idyllic village of Wayanad, Valli unfolds, seamlessly weaving together the essence of the locale. The traditional art forms, oral histories, dance, music, and divine invocations play a crucial role in evoking a profound sense of place. As we immerse ourselves in these cultural expressions, it becomes evident that they serve as powerful tools for analysing narrative as a spatially symbolic act, intricately mapping the memory and schema of the village. Inextricably linked to the earth, the novel foregrounds performance ecologies as a holistic interconnection of human and non-human spacetimes, thereby transforming into an intelligent discourse on spatial politics and environmental justice- a testimony to Pramod K Nayar’s description of Ecoprecarity. The paper argues that the competitive entanglement of performance ecology and spatial memory through the narrative at a literary representation level evokes a sense of ecoprecarity, which is crucial in recognition of either altering or expanding our notion of systems of sustainability. Keywords: Ecology, Ecoprecarity, Indigenous Community, Performances, Spatiality